2010
DOI: 10.1108/02651331011037511
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation of Korean MNC subsidiaries and their performance in the Chinese and Indian markets

Abstract: Purpose -The study of the market orientation of MNC subsidiaries in foreign markets has been generally limited. This paper, therefore, aims to assess the effects of market orientation on performance and the factors affecting the utilization of market orientation by foreign subsidiaries. Design/methodology/approach -Market orientation is operationalized within the context of the foreign market. Research hypotheses are tested using a sample of 168 Korean MNC subsidiaries operating in China and India, the two mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 95 publications
1
25
0
Order By: Relevance
“…Kwon [28] conducted a study on 168 Korean multinational companies (MNC) subsidiaries operating in China and India found that the role market orientation is significant in foreign subsidiary performance. The author, noted that foreign subsidiaries, which hold greater technology advantages capabilities and keep active network associations with native key entities such as governmental authorities, suppliers, and distributors, customers, are found to actively dedicate themselves to MO.…”
Section: Market Orientation and Organizational Performancementioning
confidence: 99%
“…Kwon [28] conducted a study on 168 Korean multinational companies (MNC) subsidiaries operating in China and India found that the role market orientation is significant in foreign subsidiary performance. The author, noted that foreign subsidiaries, which hold greater technology advantages capabilities and keep active network associations with native key entities such as governmental authorities, suppliers, and distributors, customers, are found to actively dedicate themselves to MO.…”
Section: Market Orientation and Organizational Performancementioning
confidence: 99%
“…Thus, by resolving these deficiencies, we seek to contribute to the literature in three ways. First, we contribute to the international business literature by drawing on organizational ambidexterity logic, the resource-based view and the dynamic capability perspective to theorize that export entrepreneurial-oriented behavior (henceforth export EOB) and export market-oriented behavior (henceforth export MOB) are complementary market-based resources that offer firms a capability to leverage existing competences to explore new possibilities in export markets (Kwon, 2010). To the best of our knowledge, no study has examined the complementarity between the two market-based resources in export markets.…”
mentioning
confidence: 99%
“…Network relationships need to be considered in strategic decisions. Kwon (2010) reported positive relationships between market orientation, technology advantage, and the performance of the foreign subsidiary in his study of Korean international firms in the Chinese and Indian markets. Subsidiaries with superior technology advantage and active network relationships had greater market orientation in the host countries.…”
Section: Brief Literature Review On Subsidiary Managementmentioning
confidence: 93%